Evaluation of the double coated recycled concrete aggregates for hot mix asphalt - Kareem, A.; Nikraz, Hamid; Asadi, H. (Elsevier BV, 2018)
The use of recycled concrete aggregates (RCAs) in pavement industry can mitigate natural aggregates shortage, promote sustainable practices and reduce construction cost. However, the engineering properties of RCAs are usually inferior to those of natural aggregates. In this investigation, a new state of the art coating technique, namely, double coating technique (DCT), is developed to improve strength and durability of the RCAs. The RCAs were firstly coated with a layer of cement slag paste (CSP) to reinforce its weak particles. Then, a second layer of Sika Tite-BE (here called ABE) was applied to reduce its water/bitumen absorption and enhance the durability. Marshall tests, indirect tensile test, indirect tensile ratio test and indirect tensile resilient modulus test were performed to evaluate intermediate AC14 mixtures made with 0%, 20%, 40% and 60% of double coated recycled concrete aggregates (DCRCAs). The results indicated that the DCT decreases the water absorption of the DCRCAs by 12.3% and 26.1% compared to uncoated RCAs and RCAs coated with CSP respectively. Also, the DCT effectively enhances moisture resistance and produces stiffness higher than 4000 MPa proposed for AC14 intermediate mix according to Australian practices.